Essays on experimental asset market - Halim, Edward (2017)
This thesis consists of three self-contained essays on experimental asset market. The first essay investigates the impacts of a compulsory insider-trading disclosure requirement and its combination with a holding rule modeled after the short-swing and restricted stock rules, on price predictability and asset mispricing. We modify the dynamic price-adjustment model of Smith et.al (1988) to account for the variation in investors’ private information. We show that informed agents produce weakly characterized price signals that undermine market learning, when they are required to reveal their transactions. This translates into less than proportional price adjustment to the revision in the expected dividend value. The introduction of illiquidity constraint aggravates asset mispricing. Market prices cease to respond to private information. This is attributable to a combination of inaccurate price signals and misleading portfolio adjustment signals delivered by the informed agents, which in turn stimulates the creation of loss-generating trade proposals and sustains price-destabilizing forces in the market. The second essay studies the determinants of asset price movement, and the consumption smoothing behaviors across markets populated with varying proportion of traders, with and without induced motive to smooth consumption. Although the asset is overpriced compared to the risk-neutral fundamental value in all sessions, the extent of mispricing and the magnitude of price movement are significantly higher when individuals without induced motive to trade are present. We also find that the price of the asset co-moves with the dividend state, with price predictability being higher in the presence of traders with induced motive to smooth consumption. Participants with income fluctuations are able to smooth their consumptions, with the inclination being more for those with smaller asset endowment. With fixed prices, traders are able to smooth consumption not only over periods but also across the dividend states. The third essay investigates how granting CEOs with stock ownership and the opportunity to trade influence CEOs’ effort and market efficiency. We implement a two by two experimental design, where the treatments are differentiated based on: (1) whether the CEOs receive 20% of the profit as cash bonus or 20% of the stock shares as endowment, and (2) whether or not the CEOs are prohibited from participating in trading in the open market. The findings suggest that to the contrary of public beliefs, stock ownership does not significantly improve the managerial effort decisions. There is, however, a greater alignment between CEO’s decisions and investors’ valuation of the firm assets. Investors anticipate the growth of the asset values, utilize information of the CEO’s portfolio adjustment to produce effective estimator of the fundamentals, and follow them closely. The forward looking trading strategy enhances the actual intrinsic value discovery process and improves market price quality. Meanwhile, we observe that granting CEO the opportunity to trade nullifies the positive growth CEO brings about to the firm values. Higher rate of change in the managerial efforts induces larger asset mispricing, greater costs of transactions and more volatile market prices.